Nitrogen manufacturing plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Two virtually unknown, nitrogenfixing plant species - Sesbania rostrata, an African shrub and Azolla, a fern from Asia - show potential for replacing chemical fertilizers and increasing crop production. Current work is designed to pave the way for...